Semaglutide single‐dose pen‐injector: Post hoc analysis of summative usability testing for weight management. Issue 11 (31st August 2021) - Klonoff, David C.; Bassock, Stephanie; Engels, Ella; Frederiksen, Marie; Marber, Matthew; Qvist, Marianne; Sparre, Thomas; Snitker, Søren
Abstract: Subcutaneous semaglutide, at a 2.4 mg once‐weekly maintenance dose, is approved in the United States for weight management in individuals with a body mass index (BMI) of 30 kg/m 2 or higher, or with a BMI of 27 kg/m 2 or higher and at least one obesity‐related co‐morbidity. To investigate the usability of the semaglutide pen‐injector in individuals who met these criteria, we report post hoc analysis of the summative (human factors validation) usability testing and safety analysis involving patients with type 2 diabetes (an obesity‐related co‐morbidity) with the same pen‐injector, limited to the 26 out of 30 patients with a BMI of 27 kg/m 2 or higher (11 pen‐injector–naïve, 15 pen‐injector–experienced) and 15 non‐pharmacist healthcare professionals (HCPs). Participants performed two simulated injections into an injection pad. No potentially serious use errors occurred. Mean subjective ease‐of‐use rating on a seven‐point scale, where 1 = difficult and 7 = easy, was 6.9 for the second injection in all three groups. These results suggest that the semaglutide pen‐injector is easy to use and not associated with serious use errors when used by pen‐injector–naïve or pen‐injector–experienced patients meeting the requirement for weight management with semaglutide treatment, and by non‐pharmacist HCPs.